High circadian stimulus lighting therapy for depression: Meta-analysis of clinical trials - Zhou, Li; Hou, Dandan; Wang, Yang; Zhou, Sicong; Lin, Yandan (Frontiers in Neuroscience, 2022)
Although bright light therapy (BLT) has been widely used in the clinical treatment of depression, the antidepressant effect of BLT is not well understood. Considering the connection between depression and disrupted circadian rhythm, we assumed the model of human circadian phototransduction could be more accurate in evaluating the efficacy of BLT for depression compared to light level and spectrum. A systematic review and meta-analysis were conducted and the CS (circadian stimulus) model was used to quantify the efficacy of lighting in BLT. Articles published up to June 2022 were searched in COCHRANE, EMBASE, MEDLINE, and Web of Science. Randomized clinical trials included articles using high circadian stimulus (H-CS, CS > 0.1) as lighting therapy for people with depressive disorder vs. a control group (CS < 0.1). The treatment effect was estimated by calculating the mean difference (MD) with 95% confidence intervals (CIs). Seven trials involving 258 participants met the inclusion criteria. In this sample size, H-CS lighting was associated with a significant reduction in depressive symptoms (MD = −5.56, 95% CI = −9.22 to −1.90, P = 0.003, I2 = 64%). According to the meta-analysis, CS can be employed for the clinical evaluation of BLT for patients with depressive disorder and exposure to H-CS lighting significantly reduced depressive symptoms among adults. A range of CS > 0.57 was obtained, during which different lighting parameter combinations (e.g., light levels, spectra, duration, and light distribution) could achieve better treatment for depression. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021253648.